F4. NO donors and haemodynamic changes in fetal growth restriction. (12th August 2016) - Tiralongo, G. M.; Pisani, I.; Vasapollo, B; Khalil, A; Vinayagam, D.; Thilaganathan, B.; Valensise, H.
Abstract: Introduction : Pregnancies complicated by fetal growth restriction (FGR) are known to be associated with a reduced expansion of maternal intravascular space and a lower cardiac output. Therapy with nitric oxide (NO) donors, in addition to plasma volume expansion (PVE) could improve maternal haemodynamic indices and pregnancy outcome. Methods : To evaluate maternal cardiovascular effects of NO donors. We enrolled 52 women with the diagnosis of FGR. Patients were divided into those treated with transdermal patches of NO donors and PVE or a control group. We obtained haemodynamic indices using an USCOM system. Results : At enrolment, the two groups were similar in terms of maternal, fetal and haemodynamic characteristics. In the group treated with NO donors and PVE, we found a significant increase in cardiac output, stroke volume and a decrease of systemic vascular resistance after therapy (see table). At birth the treated group also gave birth to babies with higher birth weight centile. Conclusions : The combined therapeutic approach of NO donor administration and PVE in FGR significantly improves maternal hemodynamic indices. Despite the observation nature of the data, there is suggestion that the use of NO donors together with PVE may also improve pregnancy outcome by increasing the fetal growth.